Ὁμηροκρατινίζειν (Minerva, 2019)
In Old Comedy we often find elements that belong to other literary genres used with a comic purpose. Cratinos is not a exception. In the present study we analyze the homeric elements in Cratinos' fragments, not only the literary parody examples with the reappearance of the burlesque in epic episodes, but also the spoken parody examples or parodic quoting of Horneros' poetry with a comic purpose.